Literature Review and Research Gaps in Power Quality Enhancement: From Conventional Methods to Intelligent Solutions - Mohammed Nadeem Iqbal; Asini Kumar Baliarsingh; Pratap Sekhar Puhan (International Journal of Electrical Machine Analysis and Design, 2026)
Power quality (PQ) has become a critical concern in modern electrical power systems due to the rapid integration of renewable energy sources, proliferation of power electronic devices, and increasing sensitivity of loads. This paper presents a comprehensive literature review and research gap analysis of power quality enhancement techniques, ranging from conventional approaches to emerging intelligent solutions. Traditional methods, including passive filters, capacitor banks, and synchronous condensers, have been widely employed to mitigate issues such as harmonics, voltage sag, and reactive power imbalance. However, their limitations in adaptability, dynamic response, and scalability have driven the development of advanced techniques. Modern approaches utilize custom power devices such as STATCOM, Dynamic Voltage Restorers (DVR), and Active Power Filters (APFs), which provide superior performance under varying operating conditions. Furthermore, the integration of energy storage systems and distributed generation has introduced new opportunities and challenges in maintaining power quality. Recently, intelligent techniques based on artificial intelligence, machine learning, fuzzy logic, and optimization algorithms have gained significant attention for their ability to provide adaptive, real-time solutions. Despite these advancements, several research gaps remain, including the lack of standardized frameworks, high implementation costs, interoperability issues, and limited real-world validation of intelligent methods. This review critically analyzes existing techniques, compares their effectiveness, and identifies key areas requiring further investigation. The findings aim to guide researchers and practitioners in developing robust, cost- effective, and scalable solutions for enhancing power quality in future smart grids and renewable- integrated systems.
Keywords: Active Power Filter (APF); HARMONICS; Voltage Sag; power quality; renewable energy integration